Analisis Keluhan Karyawan dan Evaluasi Postur Tubuh dengan Metode Reba di CV.Allwooden Woodworking - Much. Riza Fauzi; Muhammad Yunus Slamet Wahyudi (Universitas Merdeka Malang, 2023)
CV. Allwooden Woodworking is a furniture company that has been established since November 2017, with a product ordering system, namely Make To Order (MTO). In carrying out work, many employees still complain about discomfort at work such as complaints of pain in certain body parts, this is evidenced by the Nordic Body Map (NBM) questionnaire. To solve these problems the researcher used the Rapid Entire Body Assessment (REBA) method. From the processing, it is known that the REBA score of CV employees. There are 5 Allwooden Woodworking workstations for measuring, 5 assembly workstations, 5 sanding workstations, 6 finishing workstations, and 3 cutting workstations. Recommendations for improvement offered by researchers are work desks and rest time schedule.AbstrakÂ CV. Allwooden Woodworking merupakan perusahaan furniture yang sudah berdiri sejak November 2017, dengan sistem pemesanan produk yaitu Make To Order (MTO). Dalam melakukan pekerjaan karyawan masih banyak mengeluhkan ketidaknyamanan saat bekerja seperti keluhan rasa nyeri pada bagian tubuh tertentu, hal ini dibuktikan dari kuisoner Nordic Body Map (NBM). Untuk menyelesaikan permasalahan tersebut peneliti menggunakan metode Rapid Entire Body Assissment (REBA). Dari pengolahan diketahui skor REBA karyawan CV. Allwooden Woodworking di stasiun kerja pengukuran berjumlah 5, stasiun kerja perakitan berjumlah 5, stasiun kerja pengamplasan berjumlah 5, stasiun kerja finishing berjumlah 6, dan stasiun kerja pemotongan berjumlah 3. Rekomendasi perbaikan yang ditawarkan peneliti adalah meja kerja dan penjadwalan jam istirahat.